Proceedings of the SIGCHI Conference on Human Factors in Computing Systems Common Ground - CHI '96 1996
DOI: 10.1145/238386.238482
|View full text |Cite
|
Sign up to set email alerts
|

Assessing dynamics in computer-based instruction

Abstract: We present an evaluation of a multimedia educational software system that includes text, graphics, animations, and simulations. When compared with an informationally equivalent control environment that used text and carefully selected still images, we found little evidence that the dynamic presentations enhanced student understanding of the declarative information in this lesson. Furthermore, students cannot be relied on to take full advantage of exploratory opportunities in computer-based instruction. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 13 publications
3
35
1
3
Order By: Relevance
“…As a supplement to a biology course they were taking, junior high students interacted with the Advanced Computing for Science Education (ACSE) environment, which is a multimedia program incorporating textual information, still graphics, movies, and simulations (Pane, Corbett & John, 1996). Students using the ACSE program did not perform better than students using static graphics except for a slight advantage for information presented only in the ACSE program and not during the biology course lectures.…”
Section: Failures Of Animation To Benefitmentioning
confidence: 99%
See 1 more Smart Citation
“…As a supplement to a biology course they were taking, junior high students interacted with the Advanced Computing for Science Education (ACSE) environment, which is a multimedia program incorporating textual information, still graphics, movies, and simulations (Pane, Corbett & John, 1996). Students using the ACSE program did not perform better than students using static graphics except for a slight advantage for information presented only in the ACSE program and not during the biology course lectures.…”
Section: Failures Of Animation To Benefitmentioning
confidence: 99%
“…Even more damaging to the motivation hypothesis is that animations are not universally preferred, and are often not used (e.g. Pane et al, 1996). Finally, and to foreshadow our next point, many animations, even elegant and natural ones, are difficult to perceive and understand, except perhaps by experts with extensive experience (e.g.…”
Section: Failures Of Animation To Benefitmentioning
confidence: 99%
“…The analysts were given two documents with which to do their analyses: the 35-page user interface specification of the ACSE multimedia authoring system, Figure 2, (Gallagher & Meter, 1993) and a 55-page target multimedia document (Pane, Corbett & John, 1996). They were also given two forms to fill out as they did their analyses: a diary form (adapted from Rieman, 1993) and a problem description report (PDR, adapted from Jeffries, Miller, Wharton & Uyeda, 1991).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…These tasks were constructed from an actual biology lesson built with an earlier version of the Builder (Pane et al, 1996). We included creation and John & Marks p. 11 Tracking the Effectiveness of Usability Evaluation Methods modification tasks and exercised the major features of the Builder (text, graphics, animation, code, table of contents, glossary, bookmarks, etc.).…”
Section: Tasksmentioning
confidence: 99%
“…However, many studies have found that animations by themselves do not improve performance (Byrne, Catrambone, & Stasko, 1999;Mayer & Anderson, 1991;Palmiter & Elkerton, 1993;Palmiter, Elkerton, & Baggett, 1991;Rieber, Boyce, & Assad, 1990) unless they provide more information than static images (Pane, Corbett, & John, 1996;Tversky, Morrison, & Betrancourt, 2002). The finding that animations by themselves do not improve performance has led many researchers to question their usefulness (Palmiter & Elkerton, 1993;Pane et al, 1996), suggesting that animations should be used only in very limited situations, i.e. only when necessary and when the animation is not too difficult to use (Betrancourt & Tversky, 2000).…”
Section: Security Classification Of: 17 Limitation Of Abstractmentioning
confidence: 99%